Is there a need for a forest restoration certification scheme? - Loo, J.A.; Jalonen, R.; Thomas, E.; Bozzano, M. (Food and Agriculture Organization of the United Nations, 2015)
We propose the development of a certification scheme for forest ecosystem restoration that aims for the adoption of protocols and guidelines to ensure the sustained ecological and social value of restored ecosystems. Despite an accumulation of experience on ecosystem restoration over the past decades, it is still common to measure the success of restoration mainly in terms of number of seedlings planted or their survival in the short term. A strong focus on planting targets may divert attention from the actual objectives: establish self-sustaining forested ecosystems that provide livelihood or other ecosystem service benefits to local people. Two important determinants of short and long term success, which often do not receive sufficient attention, are matching the right seed source to the planting site conditions and ensuring that restored populations of trees have sufficient genetic variability to be self-sustaining. Because of the enormous scale of land degradation and the funds being pledged to tackle it, standardized measures of success are of increasing importance. Restoration success needs to be evaluated in a holistic way by restoration practitioners, government institutions, civil society organizations, private sector and, importantly, funding agencies. Much is known about how to restore ecosystems in different regions and under different conditions, however currently there is no consensus on what success looks like or what the minimum criteria should be for monitoring and documenting success. Success can be achieved by following well defined practices and protocols (eg by ensuring high diversity both at species and genes levels, number of mother trees for the collection of reproductive material, provenance, etc) during the various phases of the restoration process. We make a case for the development of a certification system to support long term value of restored populations for global application.